Cue-reactivity targeted smoking cessation intervention in individuals with tobacco use disorder: a scoping review - Luo, Miaoling; Gan, Quan; Fu, Yu; Chen, Zhuangfei (Frontiers in Psychiatry, 2023)
Objectives: Cue-reactivity is a critical step leading to the emergence of addictive psychology and the triggering of addictive behaviours within the framework of addiction theory and is considered a significant risk factor for addiction-related behaviours. However, the effect of cue-reactivity targeted smoking cessation intervention and the cue-reactivity paradigms used in the randomized controlled trials varies, which introduces more heterogeneity and makes a side-by-side comparison of cessation responses difficult. Therefore, the scoping review aims to integrate existing research and identify evidence gaps. Methods: We searched databases in English (PubMed and Embase) and Chinese (CNKI and Wanfang) using terms synonymous with ‘cue’ and ‘tobacco use disorder (TUD)’ to April 2023, and via hand-searching and reference screening of included studies. Studies were included if they were randomised controlled trials taking cue-reactivity as an indicator for tobacco use disorder (TUD) defined by different kinds of criteria. Results: Data were extracted on each study’s country, population, methods, timeframes, outcomes, cue-reactivity paradigms, and so on. Of the 2944 literature were retrieved, 201 studies met the criteria and were selected for full-text screening. Finally, 67 pieces of literature were selected for inclusion and data extraction. The results mainly revealed that non-invasive brain stimulation and exercise therapy showed a trend of greater possibility in reducing subjective craving compared to the remaining therapies, despite variations in the number of research studies conducted in each category. And cue-reactivity paradigms vary in materials and mainly fall into two main categories: behaviourally induced craving paradigm or visually induced craving paradigm. Conclusions: The current studies are still inadequate in terms of comparability due to their heterogeneity, cue-reactivity can be conducted in the future by constructing a standard library of smoking cue materials. Causal analysis is suggested in order to adequately screen for causes of addiction persistence, and further explore the specific objective cue-reactivity-related indicators of TUD.